2020
DOI: 10.1080/00102202.2020.1780582
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CO2/N2 Dilution on Characteristics of Liquid Fuel Combustion in Flameless Combustion Mode

Abstract: This paper presents the effect of CO 2 and N 2 dilution in the oxidizer stream on combustion and emission characteristics in a flameless combustor operating with kerosene and biodiesel as a fuel. The thermal input is varied from 30 kW (7.5 MW/m 3 ) -53 kW (13.3 MW/m 3 ) and inlet air temperature are varied from 300 K to 800 K. CO 2 /N 2 are added to dilute the oxidizer stream in a proportion of 15% of total air volume to reduce the O 2 concentration in the air stream. Reacting and nonreacting flow simulations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…On the basis of the studies ,, mentioned above, it can be concluded that the operating parameters, e.g., the air preheating temperature, the fuel type, the fuel–air premixing pattern, and the fuel–air equivalence ratio, all substantially influence the in-furnace liquid fuel MILD combustion characteristics. Several significant and relevant points can be drawn as follows: (1) The high temperature air preheating is not necessary for MILD combustion.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the basis of the studies ,, mentioned above, it can be concluded that the operating parameters, e.g., the air preheating temperature, the fuel type, the fuel–air premixing pattern, and the fuel–air equivalence ratio, all substantially influence the in-furnace liquid fuel MILD combustion characteristics. Several significant and relevant points can be drawn as follows: (1) The high temperature air preheating is not necessary for MILD combustion.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the fundamental research on the open JHC flames, the MILD combustion of firing liquid fuels has also been experimentally investigated in the closed furnaces for its establishment, emissions, and combustion characteristics. ,, Table summaries the experimental conditions performed by several research groups ,, during the years from 2004 to 2020. The previous studies mainly burned diesel, kerosene, and gasoline.…”
Section: In-furnace Mild Combustion Of Liquid Fuelsmentioning
confidence: 99%
See 3 more Smart Citations